Understanding the burden of antibiotic resistance: a decade of carbapenem-resistant Gram-negative bacterial infections in Italian intensive care units - Scaglione, Giovanni; Perego, Matilde; Colaneri, Marta; Genovese, Camilla; Brivio, Fabio; Covizzi, Alice; Viaggi, Bruno; Bandera, Alessandra; Gori, Andrea; Finazzi, Stefano; Palomba, Emanuele (Frontiers in Microbiology, 2024)
In patients admitted to intensive care units (ICUs), Gram-negative bacteria (GNB) infections pose significant challenges due to their contribution to morbidity, mortality, and healthcare costs. During the SARS-CoV-2 pandemic, Italy witnessed a rise in healthcare-associated infections (HAIs), with GNBs involved in a substantial proportion of cases. Concerningly, carbapenem-resistant GNBs (CR-GNBs) have increased worldwide, posing therapeutic challenges. This retrospective multicentre study analyzed data from over 299,000 patients admitted to Italian ICUs from 2013 to 2022. The study revealed an average of 1.5 infections per patient, with HAIs peaking during the pandemic years. Ventilator associated pneumonia (VAP) emerged as the most common HAI, with Klebsiella spp. and Pseudomonas aeruginosa predominating. Alarmingly, CR-GNBs accounted for a significant proportion of infections, particularly in VAP, bloodstream infections, and intra-abdominal infections. These findings underscore the pressing need for enhanced infection control measures, particularly in the ICU setting, to mitigate the rising prevalence of CR-GNBs and their impact on patient outcomes. The study provides valuable insights into the epidemiology of HAIs in Italian ICUs and highlights the challenges posed by CR-GNBs, especially in the context of the SARS-CoV-2 pandemic, which exacerbated the issue and may serve as a crucial example for the management of future viral pandemics 1